Comparison of Welding Results Using Oxy Acetylene Welding (OAW) and Gas Metal Arc Welding (GMAW) on Brass Leaf Propeller Repair - Mochamad Yusuf Afandi; Dwisetiono (Universitas Medan Area, 2024)
Propeller is one of the means of producing thrust to propel ships. In sailing in sea or river waters, ship propellers often hit foreign objects floating or floating in the waters which cause damage to the propeller in the form of bent, cracked or broken propeller blades. The purpose of this study is how to compare the results of welding Oxy Acetylene Welding (OAW) and Gas Metal Arc Welding (GMAW) against testing on the repair results of propeller blades made of Brass (Brass). To find out the results of welding Material testing Destructive Test (DT) Results of the maximum tensile strength (ultimate tensile strength) in Gas Metal Arc Welding (GMAW) welding of 342,368 MPa, Results of Gas Metal Arc Welding (GMAW) hardness strength of 101 HB, Results from Impact Gas Metal Arc Welding (GMAW) of 0.850 j/mm2 and the Non-Destructive Test (NDT) results from metallographic observations of the finer grains, the grande size looks small, then the composition is homogeneous, so the structure is stronger and more ductile.